Supplier Delivery Performance in Ugandan Public Procurement Contracts - Ntayi, Joseph M.; Namugenyi, Irene; Eyaa, Sarah (Journal of Public Procurement, 2010)
The purpose of this paper is to develop a comprehensive framework of achieving supplier delivery performance based on contract governance mechanisms, justice perceptions and ethical behavior using cross sectional survey data from public procuring and disposing entities (PDEs) in Uganda. Public procurement contract governance covers the design, development, implementation and enforcement of contracts. It serves to align interests of the contracting parties, reduce opportunistic behavior, lower transaction costs, promote justice perceptions, improve ethical behavior and achieve value for money procurement. Poorly managed procurement contracts result in conflicts, yet in many developing countries only rich suppliers can afford to resolve disputes through courts. For other suppliers, justice is out of reach. While it has been assumed that contracts result in good performance, little research has been carried out to corroborate this assumption. In this paper we provide theoretical, empirical and policy implications of supplier delivery performance.
Keywords: Supplier Delivery Performance; Ugandan Public Procurement Contracts